Screening interiority : dream, the unconscious, emotion and imagination in cinematic language - Rickards, Meg Frances (Centre for Film and Media Studies, 2015)
The portrayal of film characters' inner experience ensures a level of audience engagement often precluded in primarily plot-driven narratives. Yet, there is a prevailing notion that interiority is the exclusive domain of literature. To counter this pedagogy, the thesis explores how filmmakers can externalise dream; the unconscious; emotional journeys, and the realm of the imagination through cinematic language. The study draws on a theoretical framework that incorporates psychoanalytic film theory, neo-formalism and literary theory, and which engages to some extent with authorship. The compatibilist methodological approach draws on these modes of analysis, while systematically bridging theory and practice. The thesis dovetails with a creative component - the screenplay of Zinzi and the Boondogle, a children's feature film. Through this case study, the thesis examines the largely undocumented relationship between film theory and analysis on the one hand, and screenwriting and film production on the other. The research explores a number of areas germane to the screenplay, starting by uncovering innovative ways in which dreams can illuminate character interiority. It finds that animation, in its ability to render visible the metaphysical, is a compelling means of screening inner processes. Jan Svankmajer blends live action filmmaking with animation to bespeak the interpenetration of the conscious and unconscious realms. Hayao Miyazaki uses anime to construct otherworldly realms that reflect adolescent girls' rites of passage. In films that draw on African storytelling, animation is shown to make manifest the imaginative realm. Finally, the adaptation of the screenplay Zinzi and the Boondogle into a novel tests ways in which cinema and literature can divergently - but equally - evoke characters' interior lives. The thesis counters the pedagogy which insists that film is suited only to external action. Rather, the research reveals potent cinematic means of evoking oneiric and fantasy lives - bridging the traditional chasm between film theory and praxis and inviting further meetings between these discourses.